Farmer Participatory Problem Identification: a case study of Karnal District, Haryana - S R K Sing; Arindam Dhali; Debashish Mandal; Vinod Bhargav (Journal of Agricultural Extension Management, 2025)
Adequate food grain production (212 million tonnes) along with sufficient buffer stock (70 million tonnes) is a testimony of an effective agricultural research and extension system in India. This success can be attributed to the relentless efforts made by the scientists, extensionists, farmers and development agencies towards agricultural development. The ultimate goal of the National Agricultural Research System in India is to develop the most suitable technologies for the end-users through its multi-location research. Further, technological advancement in agriculture is aimed at increasing production efficiency with higher returns to the Indian farmers